Exploration of the Gas Adsorption/Selection Behavior and Its Doping Regulation Strategy of COFs for Improved Gas-Sensing Performance - Xuefeng Liang (3838222) (2025)
To understand the gas-sensing mechanism of COFs and explore an effective modulation way to regulate their sensing properties, the adsorption and sensing behaviors of NO2, NO, SO2, O2, H2O, CO2, H2S, CO, N2, and NH3 gas molecules on the surface of pristine and n-doped (Na-adsorption) Tr-Th COFs are explored theoretically with first-principles calculations in this work. Attributed to the lowest unoccupied molecular orbital (LUMO) energy level of NO2, the adsorption of NO2 on Tr-Th leads to a larger increase in carrier concentration increment (n = 1.79 × 1012 to 6.26 × 1010 cm–2) and a greater work function shift (ΔΦ = 0.178 eV) compared to other gases, which suggest that Tr-Th is a highly promising material for NO2 sensing applications. n-Type doping elevates the Fermi level of COFs, resulting in a greater carrier concentration increment (n = 1.83 × 1012 cm–2 ∼ 2.52 × 1012 cm–2) and a larger work function shift (ΔΦ = 0.08 eV ∼ 0.30 eV) upon exposure to NO2, NO, SO2, or O2 compared to other gases. It means that apart from NO2, NO, SO2, and O2 gases will also trap electrons in n-doped Tr-Th COFs, increase the electrical resistance dramatically, and then quench the source leakage current of the COFs-FET gas sensor. Our study provides more detailed information about the gas-sensing mechanism of COFs and highlights the key role that surface doping strategy plays in regulating the gas adsorption and selection behaviors for its practical gas sensor applications.